Religious Entrepreneurs? A Conversation with Nile Green. - Burton, Howard (Ideas Roadshow Conversations Ser., 2021)
This book is based on an in-depth filmed conversation between Howard Burton and Nile Green who holds the Ibn Khaldn Endowed Chair in World History at UCLA. Nile Green is an expert on Islamic History and religion in the world. He has traveled extensively in India, Turkey, Pakistan, China, Myanmar, Iran, Egypt, Yemen, Syria, Morocco and many more countries, to get a deep sense of the reality of situations on the ground. The basis of this wide-ranging conversation is Nile Green's book Terrains of Exchange which is not only an account of how the Christian missionary movement affected the developme.